DESIGN OF LIQUID BERTH STRUCTURE DOLPHIN-TYPE IN DUMAI, RIAU - Safitri Noerbaeti, Dwi
Dumai is one of the cities which have large contribut in terms of the number of oil palm plantations in Riau Province. The planned construction of a liquid bulk dock in Dumai, Riau with the type of dolphin dock was made to support the distribution of liquid bulk. The berth is planned to consist of loading platform, breasting dolphin, mooring dolphin, trestle and catwalk. In this Final Project will be discussed regarding the design steps and design of the berth for the dimensions of the structure and its elements. Calculation for dimensions of the berth structure elements is determined by checking its strength against the load that worked. Berth planning is carried out by considering aspects of environmental, operational data and the availability of the components of the berth element structure in the world. The environmental data used is processed first with several methods such as extreme value analysis, hindcasting and plot data in the form of tables, graphs and images. The processed data is used as input for load calculation and dimension calculation along with operational and material data. Structural analysis was performed using SAP2000 software with the AISC 360-16 standard code. Inputs needed are material data, dimensions of structural elements, structural layouts and loads. The output obtained in the form are Unity Check Ratio (UCR), deflection, internal forces and placement reactions. UCR and deflection values are requirements in analyzing the structure, to get the UCR and deflection values that meet the standards it is necessary to iterate by changing the dimensions and layout of the dock structure elements. While the internal forces and placement reactions will be used for the calculation of flexural, shear, dowel and spiral reinforcement in the dock structural elements namely beams, plates, pile cap and pile plug.